2010
DOI: 10.1681/asn.2010010116
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Prolyl Hydroxylases Increases Erythropoietin Production in ESRD

Abstract: The reasons for inadequate production of erythropoietin (EPO) in patients with ESRD are poorly understood. A better understanding of EPO regulation, namely oxygen-dependent hydroxylation of the hypoxia-inducible transcription factor (HIF), may enable targeted pharmacological intervention. Here, we tested the ability of fibrotic kidneys and extrarenal tissues to produce EPO. In this phase 1 study, we used an orally active prolyl-hydroxylase inhibitor, FG-2216, to stabilize HIF independent of oxygen availability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
252
1
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(267 citation statements)
references
References 35 publications
(26 reference statements)
5
252
1
9
Order By: Relevance
“…We observed that the small-molecule PHD2 inhibitor Fg4497, which was used to activate HIF2α signaling, prevented pulmonary edema and significantly improved mortality in experimental models of sepsis-induced ARDS. Since the same PHD inhibitor is being used in early clinical trials to treat anemia in patients with chronic kidney disease (49), this may also be a feasible and novel approach to treat ARDS patients.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the small-molecule PHD2 inhibitor Fg4497, which was used to activate HIF2α signaling, prevented pulmonary edema and significantly improved mortality in experimental models of sepsis-induced ARDS. Since the same PHD inhibitor is being used in early clinical trials to treat anemia in patients with chronic kidney disease (49), this may also be a feasible and novel approach to treat ARDS patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, differential expression of hypoxia-inducible factor (HIF) proteins, of globin transcription factor proteins, or hypermethylation of regulatory elements has been suggested to be involved (48,50). Relevance of such knowledge lies in possible use of these pathways to rescue endogenous Epo production in anemic patients (51).…”
Section: Regulation Of Epo Productionmentioning
confidence: 99%
“…Patients with end-stage renal disease require life-long therapy with recombinant EPO (rhEPO), but currently, therapeutic approaches for enhancing endogenous non-renal production of EPO is of high interest, as discussed in recent reviews [5,6]. Pharmacological manipulation of the hypoxia-inducible transcription factor (HIF) has been shown to stimulate endogenous EPO production [7]. Methods for up-regulating production of EPO from the liver seem especially attractive as an alternative to therapy with rhEPO when kidney production has ceased [8].…”
Section: Introductionmentioning
confidence: 99%